2007
DOI: 10.1590/s0036-46652007000500005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of HPV 16 and 18 in cervical samples of patients from Belo Horizonte, Minas Gerais, Brazil

Abstract: SUMMARYPurpose: The aim of this study was to investigate the frequency of HPV infection and the types 16 and 18 in cervical samples from patients attended at two public health services of the city of Belo Horizonte, MG. Methods: Cervical samples from 174 patients were collected for cytopathological and molecular tests. HPV infection was searched by PCR utilizing MY09 and MY11 primers or HPV 16 and HPV 18 specific primers. Results: Amongst the 174 samples analyzed, 20.7% presented squamous intraepithelial and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
6
1
4
Order By: Relevance
“…Evidence of the deficiencies of the national CC screening program is illustrated by a study in Southern Brazil with 5,485 women in whom previous cytology was reported by 100% of the women diagnosed with carcinoma, while Pap smear in a previous period of less than 3 years was referred by, respectively, 86.5% and 92.8% of women with abnormal cytology and histology (23) . In the present study, HPV DNA was detected in 100% of LSIL and HSIL cases, similar to that reported by Freitas et al (24) , who detected HPV in 93.3% of LSIL. Possibly, the use of MY/GP+ in PCR nested system has increased the sensitivity, as reflected by the additional 27 samples (in 162) found to be HPV reactive.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Evidence of the deficiencies of the national CC screening program is illustrated by a study in Southern Brazil with 5,485 women in whom previous cytology was reported by 100% of the women diagnosed with carcinoma, while Pap smear in a previous period of less than 3 years was referred by, respectively, 86.5% and 92.8% of women with abnormal cytology and histology (23) . In the present study, HPV DNA was detected in 100% of LSIL and HSIL cases, similar to that reported by Freitas et al (24) , who detected HPV in 93.3% of LSIL. Possibly, the use of MY/GP+ in PCR nested system has increased the sensitivity, as reflected by the additional 27 samples (in 162) found to be HPV reactive.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed an HPV prevalence of 39.5%, similar to the 39.6% prevalence obtained using consensus primers PCR findings in a population from Minas Gerais (24) , Brazil, but higher than observed in a regular screening high-risk population in São Paulo (26) , in whom 13.8% of the subjects were HPV positive by consensus primers PCR. Off course the variation in the prevalence rates, when controlled by the HPV determination method, derives from the characteristics of the population, mainly age and sexual activity.…”
Section: Discussionsupporting
confidence: 85%
“…Because HPV-16 and -18 are the most frequent types associated with SIL and invasive cervical lesions in Brazil, [28][29][30] attention was focused on them, using previously described specific primers and conditions. 31 The absence of amplification by HPV-16 or -18 primers but the presence of amplification by the MY09 and MY11 primers did not exclude the presence of other HPV types, which in this study were designated as HPVX.…”
Section: Hpv Detection and Typingmentioning
confidence: 99%
“…In this study, the n-PCR technique was used, which combines two diVerent pairs of consensus primers. The advantage of this last technique is the substantial increase in sensitivity [10,15]. However, we cannot exclude the possible contribution of still undeWned genetic factors in the diVerent populations studied.…”
Section: Discussionmentioning
confidence: 95%